Employment relations, the state and transitions in governance in Myanmar - Gillan, M.; Thein, Htwe Htwe (Sage Publications, 2016)
Myanmar is undergoing a wide-ranging process of reform which in employment relations has allowed for the formation of a nascent labour movement as well as employer organisations and industrial tribunals. The introduction of reformist labour regulation and official tolerance for worker representation should not be interpreted as constituting a turn towards a state where the interests of labour are a priority: the imperative to extend and reform workers’ collective and individual rights, employment conditions and labour standards has stemmed more from external influence than it has internal legitimation pressures. Nevertheless, as this article demonstrates, the boundaries and even the viability of labour regulation and employment relations in Myanmar will be determined by the organisational dynamics of these parties and the strategic choices they make as to how to serve their interests and objectives.